Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/agronomy8120304
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fertilizer Management Strategies Aiming to Increase Nitrogen Use Efficiency of Wheat Grown Under Conservation Agriculture

Abstract: Sustainable crop production systems can be attained by using inputs efficiently and nitrogen use efficiency (NUE) parameters are indirect measurements of sustainability of production systems. The objective of this study was to investigate the effect of selected nitrogen (N) management treatments on wheat yields, grain and straw N concentration, and NUE parameters, under conservation agriculture (CA). The present study was conducted at the International Maize and Wheat Improvement Center (CIMMYT), in northwest,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…The effects of organic manure and biofertilizers amendments on grain yield and 1000-grain weight varied in different studies. Research [31,42] reported that the grain yield and 1000-grain weight of maize received a half dose of N (102.75 Kg ha −1 ) fertilizer and biofertilizers were 13% and 10% greater than that in treatment with a full dose of N fertilizer (175 kg N ha −1 ), respectively. On the contrary, two studies revealed that biofertilizers and half dose of N fertilizer produced 25% and 17% less in grain yield and 1000-grain weight compared with that received a full dose of N fertilizer [26,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of organic manure and biofertilizers amendments on grain yield and 1000-grain weight varied in different studies. Research [31,42] reported that the grain yield and 1000-grain weight of maize received a half dose of N (102.75 Kg ha −1 ) fertilizer and biofertilizers were 13% and 10% greater than that in treatment with a full dose of N fertilizer (175 kg N ha −1 ), respectively. On the contrary, two studies revealed that biofertilizers and half dose of N fertilizer produced 25% and 17% less in grain yield and 1000-grain weight compared with that received a full dose of N fertilizer [26,38].…”
Section: Discussionmentioning
confidence: 99%
“…Research [25,26] reported that the wheat grain yields were comparable in the treatments that received 80 t ha −1 yr −1 of organic manure or 204-252 kg N ha −1 yr −1 chemical N-fertilizers. As for biofertilizers, [27][28][29] reported that application of one biofertilizers obtained from sewage sludge at 7.2 L ha −1 increased maize grain yield by 17% compared with the untreated control and [10,30,31] revealed that biofertilizers amendments reduced inorganic N-fertilizers by 25% without decreasing rice yield in India [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The means for N concentration, N yield and NHI (over all treatments and both years) were: GNC-2.62%, SNC-0.43%, NY GRAIN -127.7 kg N ha −1 , NY STRAW -25.6 kg N ha −1 , NY AGB -153.3 kg N ha −1 and NHI-82.9% (Table 5). 2 Urea with nitrification inhibitor, 3 Incorporated Urea, 4 Liquid urea ammonium nitrate, 5 Analysis of variance, 6 Different letters indicate significant differences. Significant effects: p < 0.05 (*), p < 0.01 (**) and p < 0.001 (***), 7 Not significant.…”
Section: N Concentration N Yield and N Harvest Indexmentioning
confidence: 99%
“…Nitrogen management in agriculture aims to achieve agronomic objectives (farm income, high crop and livestock productivity) and environmental objectives (minimal N losses) simultaneously. Nitrogen use efficiency (NUE) and their components are indirect measurements of the sustainability of cereals production systems [2][3][4]. Improving the NUE, especially the fraction of N input harvested as product, is one of the most effective means of increasing crop productivity while decreasing environmental degradation [5].…”
Section: Introductionmentioning
confidence: 99%